En negro y blanco : fotografías del Cordobazo al juicio a las juntas - Cerolini, Pablo; Reynoso, Héctor Alejandro; Durán, Jorge 1942-; Nun, José 1934- (Secretaría de Cultura, Presidencia de la Nación, 2006)
A collection of never published white and black photographs by 43 photojournalists from 15 news archives that document with appalling images of the "Dirty War" from the violent repression against the insurrectional movement known as the "Cordobazo" in 1969 to the judicial process in 1985 of the military dictatorship's former leaders, officers and enlisted men who carried out the "disappearances," torture, and killings of Argentine workers, intellectuals, and students